STRATEGI INDUSTRI KECIL MENENGAH KOMPONEN OTOMOTIF (STUDI KASUS PT PQR): INDUSTRIAL STRATEGY FOR SMALL MEDIUM ENTERPRISES IN AUTOMOTIVE COMPONENTS INDUSTRY (CASE STUDY IN PT PQR) - Dian Rinaldy; Alla Asmara; Muhammad Findi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
This study analyzed PT PQR's external conditions and strategic factors that arose, analyzed PT PQR's internal conditions, formulated alternative strategies for PT PQR, and determined strategic priorities for PT PQR. The strategic planning phase began with an external analysis that developed with a PEST analysis and Porter's Five Forces. Later on, we performed an internal analysis. The strategic business planning performed I-E and TOWS matrices and the Quantitative Strategic Planning Matrix (QSPM). The external analysis results identified growth, customer loyalty, and ATPM competition as opportunities, while exchange rate fluctuations, import policies, and newcomer meetings were the challenges. The internal analysis results found product quality, competitive selling prices, and production capacity as the strengths, while low productivity, workplace accidents, and the quality of human resources were identified as weaknesses. The IE matrix combined IFE value of 2,346 and EFE value of 2,178 to position PT PQR in quadrant V. Therefore, the strategy was to hold and maintain. The eight alternative strategies for PT PQR were product development strategy, market development, improvement in production management, HR development, Quality management implementation, development of higher capacity machines, inventory management, and improvement of Production Operation Standards (SOP). Market development strategies with new ATPM market development and product development strategies with diversified furniture products were two priority strategies that were complemented by short and long term action plans in implementing these strategies. Keywords: PEST analysis, IKM, EFE, IFE, Matriks IE, Matriks TOWS, QSPM Abstrak: Penelitian ini bertujuan menganalisis kondisi eksternal PT PQR dan faktor strategis yang timbul, menganalisis kondisi internal PT PQR, merumuskan alternatif strategi bagi PT PQR, serta menentukan prioritas strategi bagi PT PQR. Tahap perencanaan strategis diawali dengan analisis eksternal yang dikembangkan dengan analisis PEST dan analisis industri menggunakan Lima Kekuatan Porter lalu diikuti analisis internal. Sementara untuk merancang strategi bisnis digunakan matriks I-E dan matriks TOWS dengan Quantitative Strategic Planning Matrix (QSPM). Hasil analisis eksternal mengidentifikasi pertumbuhan permintaan, loyalitas pelanggan, dan persaingan ATPM sebagai peluang sementara fluktuasi nilai tukar, kebijakan impor, dan kehadiran pendatang baru adalah ancaman utama. Hasil analisis internal mengidentifikasi kualitas produk, harga jual yang kompetitif, dan kapasitas produksi adalah kekuatan utama, sementara produktivitas rendah, kecelakaan di tempat kerja, dan kualitas sumber daya manusia sebagai kelemahan. Matriks IE memadukan IFE 2,346 dan EFE 2,178 untuk memposisikan PT PQR dalam kuadran V dan rekomendasi strategisnya adalah pertahankan dan pelihara. Delapan alternatif strategi bagi PT PQR adalah strategi pengembangan produk, pengembangan pasar, perbaikan dalam manajemen produksi, pengembangan SDM, penerapan manajemen Mutu, investasi mesin berkapasitas lebih tinggi, pengelolaan inventori, dan peningkatan Standar Operasi Produksi (SOP). Strategi pengembangan pasar dengan memasuki pasar ATPM baru dan strategi pengembangan produk dengan diversifikasi produk furnitur adalah dua strategi prioritas yang dilengkapi dengan rencana tindakan dalam jangka pendek dan panjang untuk mengimplementasikan strategi-strategi tersebut. Kata kunci: Analisis PEST, IKM, EFE, IFE, Matriks IE, Matriks TOWS, QSPM